2018
DOI: 10.3390/app8020310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Synthesis Activation and Relative Humidity on Adsorption Performance of ZIF-8 for Capturing Toluene from a Gas Phase in a Continuous Mode

Abstract: Zeolitic imidazolate framework-8 (ZIF-8) was used as an adsorbent for the removal of toluene in its gas phase at different relative humidity (RH). High-purity ZIF-8 with an average particle size of 0.64 µm synthesized from an aqueous solution at room temperature, and then characterized by X-ray diffraction (XRD), fourier transform infrared (FT-IR) and scanning electron microscopy (SEM) techniques. Dynamic adsorption (continuous mode) experiments of toluene on ZIF-8 were studied using breakthrough curves. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…After coated with ZIF-8 ( Figure 3b), both peaks representing the FA and ZIF-8 could be found in the composite. New infrared diffraction peaks at 3136, 2930, 1584, 1426 cm −1 are feature peaks of imidazole, and the infrared diffraction peak at 500 cm −1 is the peak of Zn-O telescopic vibration, which is consistent with the earlier published papers [28,29]. Moreover, the band at 3444 cm −1 disappeared and C-H stretching vibration adsorption peak of methyl and imidazole ring appeared in 3136 and 2930 cm −1 [28], respectively.…”
Section: Ftir Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…After coated with ZIF-8 ( Figure 3b), both peaks representing the FA and ZIF-8 could be found in the composite. New infrared diffraction peaks at 3136, 2930, 1584, 1426 cm −1 are feature peaks of imidazole, and the infrared diffraction peak at 500 cm −1 is the peak of Zn-O telescopic vibration, which is consistent with the earlier published papers [28,29]. Moreover, the band at 3444 cm −1 disappeared and C-H stretching vibration adsorption peak of methyl and imidazole ring appeared in 3136 and 2930 cm −1 [28], respectively.…”
Section: Ftir Analysissupporting
confidence: 88%
“…In addition, the peaks at 1350-1500 cm −1 belong to the entire ring stretching. The in-plane bending of the ring are found at 900-1350 cm −1 while those below 800 cm −1 are associated with the out-of-plane bending of the ring [29]. Considering the above analysis, the preparation mechanism of ZIF-8/FA composites can be explained by Figure 4…”
Section: Ftir Analysismentioning
confidence: 87%
“…For ZIF-8, the IRRA spectrum, Figure 8b, shows a strong absorption band at 1587 cm −1 , assigned to the CN stretching. [15,[29][30][31] Further intense bands around 1300-1500 cm −1 overlap with the absorption bands of the stretching of imidazole rings. [32] The vibration bands are essentially constant and are not affected by exposing the sample to air.…”
Section: Vibrational Spectroscopy and Discussion Of Degradationmentioning
confidence: 92%
“…[5] Studies on ZIF-8 powders have found the materials are suitable adsorbents for several applications including vapor phase hydrocarbon capture [6][7][8] and liquid-phase contaminant extraction. [9,10] Due to the hydrophobicity of the 2-methylimidazole linker, ZIF-8 has been found to have low affinity toward water vapor, [6,11] making it particularly suitable for adsorption applications where humidity's competition for adsorption sites plays a key role, [12,13] such as indoor air cleaning of volatile organic compounds (VOCs). [14][15][16] ZIF-67 has been found to be unstable in liquid water, with a noted loss in crystallinity, [17] and water vapor isotherms of the material have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%